Using artificial intelligence applications in Islamic banks - advantages and risks - zekri, tawfik; abdedaim, azzeddine (Journal of Social Sciences and Humanities, 2025)
The Fourth Industrial Revolution resulted in many advanced technologies and complex technologies. Which brought about a qualitative shift and a major breakthrough in all fields and various sectors. At the forefront of these technologies, and at the top of these innovations, is what is called artificial intelligence, which has brought about a major revolution in contemporary life. Because of its great ability to simulate human intelligence and perform many complex tasks and arduous jobs, without the need for human intervention in the military, technical, medical, financial, or other fields. In this study, the most important basic concepts related to artificial intelligence were highlighted, then the concept of Islamic banks was explained. After that, the study focused on explaining the advantages and risks that result from employing applications of artificial intelligence in the financial and banking field, specifically on Islamic banks. The study concluded that artificial intelligence, with its various applications and technologies, has begun to play an important role in improving the work of banks in general, and Islamic banks in particular. Because of its many advantages and advantages, in addition to the fact that traditional banks and banks cannot keep pace and compete with banks that adopt advanced technologies except by adopting artificial intelligence applications. In contrast, the study pointed out a number of risks and challenges that could threaten the work of banks that adopt artificial intelligence applications in their transactions and services.